(untitled) (Research, Society and Development, 2024)
Introduction: the discovery of neck circumference was promising due to its practical applicability and relationship with cardiometabolic alterations, being a simple, low-cost measure that complements the nurse’s assessment in identifying health risks. Objective: associate neck circumference with modifiable and non-modifiable cardiovascular risk factors. Methods: descriptive, quantitative and cross-sectional study carried out in a philanthropic quaternary hospital. The convenience sample consisted of adults who underwent ultrasound of the carotid arteries and had a lipid profile, fasting blood glucose and glycated hemoglobin in their medical records. A data collection form containing sociodemographic and clinical variables was applied. Weight and height were measured on an electronic scale with a stadiometer, and neck circumference was measured in an orthostatic position, at the midpoint of the neck, considering neck circumference <37 cm for men and <34 cm for women. The associations between quantitative variables were measured by Spearman’s correlation and, among the other variables, tests such as chi-square were used. Results: the variables that showed a significant positive association with neck circumference were male gender, weight, height, body mass index, smoking and smoking history. Only HDL-c showed a significant negative association. Conclusion: neck circumference was associated with male sex, weight, height, body mass index, smoking, smoking history and HDL-c, the latter with an inversely proportional association. It proved to be a reliable tool and an important indicator of cardiovascular risk and easy to use in Public Health services.